Adaptação de conteúdos de objetos de aprendizagem para a televisão digital - Alves, Heleno da Silva (Universidade do Vale do Rio dos Sinos, 2011)
Learning Objects (LO) are assuming an important role in current educational context, where computational resources are a common presence in the classroom due to government incentives. Among the needed characteristics for right using of LOs by teachers and students, two main aspects are highlighted by the literature, the reusing and sharing. With the advances in the new computing environments the concept of reusing has been taking new proportions viewing the utilization of its educational content in several computing environments. Among these new computing environments, the mobile devices and the digital television (DTV) extends the concept of e-learning creating two new strands, they are the m-learning and t-learning respectively. Nevertheless, the LOs created for e-learning environment hardly can be used in the new environments due to the difficulties of presenting on mobile and DTV devices. To help the presenting of LOs in these new environments this work presents concepts related to LOs, DTV and agents based software aiming the analysis of a multiagent system developed. This system has as your main feature the adaptation of content for t-learning and m-learning environments. The intention of this work is present an architecture, using Agent UML (AUML) diagrams, that supports the LOs adaptation for viewing in multiple environments and apply this architecture to digital television use cases. Through the system developed should be possible to adapt multiple LOs content formats to be viewed on the devices of the Brazilian System of Digital Television (SBTVD).
Keywords: Objetos de aprendizagem; Televisão digital; Agent UML; Sistemas multiagentes; Learning objects; Digital television; Multiagents systems; ACCNPQ::Ciências Exatas e da Terra::Ciência da Computação